Learning at Covid-19 Pandemic Era: Science Technology Engineering and Mathematic Competencies and Student Character - Chaerul Rochman; Catherien Suci Ramdhini Pertiwi (Universitas Muhammadiyah Sidoarjo, 2020)
Distance learning or online learning is the recommended alternative form of learning. But it is still uncertain, what competencies are important to be mastered by students. This study aims to examine what important competency components need to be prioritized and how the relationships between these components. The research method used is a mixture of quantitative and qualitative descriptive. The subjects of this study were 32 junior high school students. This study concludes that students have the competence of Science Technology Engineering and Math (STEM), products, and characters that vary and the relationship between STEM and products is stronger than the character components.